Role of Biomechanical Parameters in Hip Osteoarthritis and Avascular Necrosis of Femoral Head - Iglič, Veronika Kralj -; Dolinar, Drago; Ivanovski, Matic; List, Ivo; Daniel, Matej (IntechOpen, 2012)
None